2020
DOI: 10.1523/jneurosci.0299-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

The Nucleus Accumbens Core is Necessary to Scale Fear to Degree of Threat

Abstract: Fear is adaptive when the level of the response rapidly scales to degree of threat. Using a discrimination procedure consisting of danger, uncertainty, and safety cues, we have found rapid fear scaling (within 2 s of cue presentation) in male rats. Here, we examined a possible role for the nucleus accumbens core (NAcc) in the acquisition and expression of fear scaling. In experiment 1, male Long-Evans rats received bilateral sham or neurotoxic NAcc lesions, recovered, and underwent fear discrimination. NAcc-le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 81 publications
1
16
0
Order By: Relevance
“…So far, no differences in VP activity/function have been found in studies that examined biological sex 19,42,43 . Our laboratory has observed complete and comparable fear discrimination in male and female rats 11,[58][59][60][61] . We predict that equivalent relative threat signaling will be observed in female and male VP neurons.…”
Section: 5 6a D and 7c)mentioning
confidence: 87%
See 1 more Smart Citation
“…So far, no differences in VP activity/function have been found in studies that examined biological sex 19,42,43 . Our laboratory has observed complete and comparable fear discrimination in male and female rats 11,[58][59][60][61] . We predict that equivalent relative threat signaling will be observed in female and male VP neurons.…”
Section: 5 6a D and 7c)mentioning
confidence: 87%
“…Brain regions essential to fear, most notably the central amygdala [1][2][3] and basolateral amygdala (BLA) [4][5][6][7][8] , must be necessary to signal and utilize relative threat. At the same time, threat learning and behavior is the product of a larger neural network 9,10 that includes brain regions traditionally implicated in reward [11][12][13][14][15] . The ventral pallidum (VP) is a compelling candidate for a neural source of relative threat.…”
mentioning
confidence: 99%
“…Furthermore, the striatum is closely interconnected with the amygdala, hippocampus, and ventromedial PFC—all key players in adolescent anxiety—and is known to be highly involved in motivation, conditioning/prediction error, and attention ( Lago et al, 2017 ). Pre-clinical animal models have demonstrated that the VS (e.g., nucleus accumbens; NAcc) is necessary for scaling fear to degree of threat: adult rats with NAcc lesions showed specific impairments in rapid uncertainty-safety discrimination, a skill that is necessary for survival and disrupted in clinical anxiety ( Ray et al, 2020 ). While future work is needed to examine whether this association holds in juvenile rats, the striatum has also been linked to anxiety in humans; anxious youth show greater striatal response to low- rather than high-valued outcomes, perhaps due to the relative level of potential risk associated with each option, in addition to demonstrating increased VS activity during feedback anticipation ( Benson et al, 2014 ).…”
Section: The Development Of Anxietymentioning
confidence: 99%
“…Given that only cued fear was evaluated in the present experiments, the lack of a NAcC inactivation effect on fear expression is perhaps not surprising. Intriguingly, recent evidence suggests that the NAcC may be recruited to aid in fear expression in situations where cue discrimination (and thus, the appropriate allocation of fear) is made more difficult by the inclusion of an ambiguous CS that is probabilistically associated with foot shock (Ray et al 2020). When viewed in light of the present data, this suggests that the NAcC may play a more prominent role in discriminative fear expression when threat is probabilistic, but not under more simple conditions when CSs are associated with shock in a deterministic manner.…”
Section: Nac: Subregion-specific Control Of Conditioned Suppressionmentioning
confidence: 99%